2022
DOI: 10.1021/acsomega.1c06890
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Biological Roles and Interactions of Cullin-5 Protein

Abstract: Ubiquitination is a modification of proteins that has a powerful impact on protein function along with other cellular functions. This reaction is regulated through major enzymes, including E3 ligase as a chief enzyme. The Cullin-5 ubiquitin ligase (Cul5) possesses a variety of substrates that maintain the process of ubiquitination as well as proteasomal degradation. It regulates cell development, proliferation, and other physiological tasks in the human body. Moreover, it has been discovered that the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…CUL5 is a Cullin-RING (CRL) E3 ubiquitin ligase that is best known for its role in regulating aspects of viral infection, especially for HI [39][40][41] . CUL5 serves as a scaffold for facilitating ubiquitin transfer from an E2 ligase to CUL5 substrates.…”
Section: Cul5 Controls Tau Levels Via Tau Ubiquitinationmentioning
confidence: 99%
“…CUL5 is a Cullin-RING (CRL) E3 ubiquitin ligase that is best known for its role in regulating aspects of viral infection, especially for HI [39][40][41] . CUL5 serves as a scaffold for facilitating ubiquitin transfer from an E2 ligase to CUL5 substrates.…”
Section: Cul5 Controls Tau Levels Via Tau Ubiquitinationmentioning
confidence: 99%
“…Cul 5 is currently regarded as a promising drug target molecule because of its various biological roles. 25 In this study we showed that Cul 5 promotes angiogenesis and cell adhesion. Cul 5 is the key component of Cullin-RING ligase-5 (CRL-5), and activation of CRL-5 requires Cul 5 neddylation, which is catalyzed by a neddylation enzyme cascade, consisting of the E1 NEDD8-activating enzyme, the E2 neddylation conjugating enzyme, and E3 neddylation ligase, 35 , 36 thus, neddylation inhibitor could inactive Cul 5.…”
Section: Discussionmentioning
confidence: 71%
“…TRAF6 is a substrate of Cul 5, 25 and it has also been reported that the Cul 5−TRAF6 interaction activates NF-κB signaling. 12 The TRAF6/NF-κB pathway is involved in many diseases, such as cancer, 31 lung injury, 32 and myocardial injury.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…mTOR signaling can be increased by K48-ubiqutination and degradation of DEP-domain containing mTOR-interacting protein (DEPTOR); a negative regulator of mTOR, able to act on both mTORC1 and mTORC2 [ 33 ]. DEPTOR is ubiquitinated either by the activity of the E3 ligases CUL5 [ 34 ] or Ring Finger Protein 7 (RNF7) [ 35 ]. This results in the increase of mTOR levels and in the inactivation of the autophagic process [ 36 , 37 ].…”
Section: Ubiquitinationmentioning
confidence: 99%